THE EFFECT OF INSTITUTIONAL OWNERSHIP, PUBLIC ACCOUNTING FIRM REPUTATION, AUDITOR INDUSTRY SPECIALIZATION PROFITABILITY, AND COMPANY SIZE ON AUDIT DELAY (STUDY IN CONSUMER GOODS COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE 2018 – 2020) - Felicia Siswanto; Sugi Suhartono (Jurnal Akuntansi, 2022)
Financial statements are important for companies because they are useful for conveying various information about the company's performance as a basis for making decisions. So that the length of time it takes the auditor to complete an audit of the financial statements can affect the decisions of users of financial statements. Therefore, the purpose of this study is to determine the influence of institutional ownership, KAP reputation, auditor industry specialization, profitability, and company size on audit delay. Hypothesis testing in this study used multiple linear regression analysis. The research object used 32 consumer goods companies in the period 2018-2020. The results showed that institutional ownership did not have enough evidence of an effect on audit delay. KAP reputation is sufficient evidence of negative influence on audit delay. Industry auditor specialization does not have enough evidence of an effect on audit delay. Profitability there is enough evidence of a negative effect on audit delay. The size of the company does not have enough evidence of an effect on audit delay.